An Analysis of Way Halim Community Preparedness Post-Flood Disaster Perspective on The Implementation Of Disaster Mitigation Management: 24 February 2024 - Andien, Andien; Zahiya, Asda Arwa; Mulyasari, Rahmi; Haerudin, Nandi (Journal of Engineering and Scientific Research, 2025)
Currently, the city of Bandar Lampung is facing a quite serious problem, namely the Flood Disaster which hit on February 24, 2024. Bandar Lampung has a diverse topography, ranging from lowlands, and beaches, to hilly areas with a height of 0-500 meters above sea level. Almost every year Bandar Lampung experiences the same problem, namely flooding in various sub-districts, one of which is the Way Halim sub-district. Floods are water that overflows and cannot be accommodated by rivers or absorbed by water catchment areas. Floods are also a disaster that can disrupt community activities. Bandar Lampung has a relatively high risk of flood disasters. Therefore, efforts need to be made to overcome the flood disaster. This research aims to analyze the preparedness of the community in the Way Halim subdistrict, Bandar Lampung after the flood disaster. This research uses an approach to community perceptions regarding preparedness in implementing disaster mitigation management. Preparedness in facing flood disasters can help communities plan actions that can be taken when floods strike. Community in Way Halim sub-district is moderately prepared for disasters. Lack of training andoutreach, results in a lack of focus during disasters. Proactive steps such as early warning systems, community education, and infrastructure development are crucial for enhancing preparedness in facing flood disasters.